Changes in maternity leave coverage: Implications for fertility, labour force participation and child mortality. (November 2019) - Ahmed, Salma; Fielding, David
Abstract: Analysing macro-panel data from 18 African and Asian countries over the period 1995–2016, this article investigates the effects of the level and duration of paid maternity leave on three dimensions of human development: fertility, female formal-sector employment and infant mortality. There is some evidence that, on average, extending the duration of leave leads to reductions in infant mortality and employment. However, there is no conclusive evidence that leave duration has a direct effect on fertility. In contrast, there is some evidence that higher maternity leave payments lead to higher fertility, but no evidence that payment levels have any effect on infant mortality or employment. Highlights: Longer duration of leave reduced infant mortality and demand for female labour. Maternity leave payments lead to higher fertility. We found significant interactions between the three development outcomes. Findings may not be generalisable to the whole of Africa and Asia.